A Single-Stage Dual Output Ac/Dc Converter With Pfc For Supplying Led Light - Bani Ahmad, Ashraf Mohammad (2017)
LED lights have become the most well-known type of lights, owing to their multiple features such as energy saving, long life-span, good luminous efficacy and low maintenance costs. LED lights are suitable for usage in various locations and fields, such as indoor or outdoor locations, and in electric vehicles. The evaluation of the performance of LED light depends on the values taken from measurement of the power factor, efficiency and total harmonic distortion of the LED driver. To achieve good values, a single-stage dual output AC/DC converter with PFC is proposed in this thesis. It can be used as two distinct types of the LED driver. When the relay switch (SWr) state is changed from turned-off (open) to turned-on (closed), the secondary-side of the proposed topology is changed from a full-bridge rectifier (type 1) to a full-bridge voltage doubler rectifier (type 2). The proposed converter consists of one LLC tank and two boost circuits with one shared inductor. The proposed converter is designed to work with 240 VAC, 50Hz single-phase input supply voltage. A high resonant frequency at 100 kHZ and a duty cycle at 48.5% were used for the switches. To simulate the proposed converter, MATLAB Simulink software was utilized. When the output power was at 100 W and the relay switch was open, the power factor, efficiency, total harmonic distortion, and bus voltage were found to be 0.99, 93.3%, 14.53%, and 338 V, respectively. When the output power was at 100 W and the relay switch was closed, the power factor, efficiency, total harmonic distortion, and bus voltage were found to be xx 0.989, 91.8%, 15.17%, and 340 V, respectively. In addition to that, the soft-switching characteristics were also achieved. The MOSFET switches are turned on during zero voltage switching (ZVS) and the secondary output diodes are turned off during zero current switching (ZCS). Furthermore, when the relay switch was closed, the output voltage was twice higher than that when the relay switch was open. This means that smaller current are flowing through the output diodes, output capacitor and transformer, which leads to reducing the stress on these components and potentially increasing their operating lifespan.